Improving The Effectiveness of Primary School Mother Tongue Lessons - Gafforjon Ruzmatovich Rakhmonov (Genius Journals, 2021)
The teacher should use simple and straightforward methods to increase the effectiveness of primary school mother tongue lessons. In addition to the scientific principle in the lessons, it is advisable to use thematic games, various multimedia programs. In doing so, the teacher should look for the equipment that students need as close as possible. Because elementary school students not only remember what is around them, but also find it easier to imagine.
Keywords: Straightforward methods; elementary school students; curriculum and standards; educational process